2018
DOI: 10.1002/cpe.4892
|View full text |Cite
|
Sign up to set email alerts
|

Research of animals image semantic segmentation based on deep learning

Abstract: It is imperative for us to develop the technology of image semantic segmentation with the increasing demand in the image processing. Nowadays, the development of deep learning is of great significance to the improvement of image segmentation. Furthermore, the paper discussed the relationship between image semantic segmentation and animal image research based on the actual situation, and found that animal image processing technology plays a more important role in the field of protecting precious animals. The en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The method of using the source code for log parsing, although highly accurate, is generally not available, because ordinary engineers cannot get the source code generating logs. In the field which researches of log analysis, a great deal of researchers did a lot of related works about detecting anomaly [21][22][23][24][25][26][27][28][29][30][31]. The most important feature of the abovementioned clustering-based log template extraction method is that when the similarity function is established.…”
Section: Related Workmentioning
confidence: 99%
“…The method of using the source code for log parsing, although highly accurate, is generally not available, because ordinary engineers cannot get the source code generating logs. In the field which researches of log analysis, a great deal of researchers did a lot of related works about detecting anomaly [21][22][23][24][25][26][27][28][29][30][31]. The most important feature of the abovementioned clustering-based log template extraction method is that when the similarity function is established.…”
Section: Related Workmentioning
confidence: 99%
“…Liu et al have discussed the relationship between image semantic segmentation and animal image research based on the actual situation, and found that animal image processing technology plays a more important role in the field of protecting precious animals. The end‐to‐end network training of this paper has consisted of Fully Convolutional Network (FCN) for the front end and Conditional Random Fields as Recurrent Neural Networks (CRF‐RNN) for the back end via comparing a variety of research methods.…”
Section: Theme Of This Special Issuementioning
confidence: 99%
“…© 2021 The Authors. The Journal of Engineering published by John Wiley & Sons Ltd on behalf of The Institution of Engineering and Technology problems such as large parameters and complex calculations due to the influence of network depth [12,13]. This leads to the problem of insufficient real-time performance for image segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of deep learning (DL) has opened up a new situation for the problem of image target segmentation and recognition, and has excellent performance for the recognition of a variety of small‐scale data sets [11]. At the same time, it is still necessary to see that traditional DL network models have problems such as large parameters and complex calculations due to the influence of network depth [12, 13]. This leads to the problem of insufficient real‐time performance for image segmentation.…”
Section: Introductionmentioning
confidence: 99%